A Unique Trinucleotide-Bloc Mutation-Based Two SARS-CoV-2 Genotypes with Potential Pathogenic Impacts - Mustak Ibn Ayub (Advances in Virology)
SARS-CoV-2, the novel coronavirus behind the COVID-19 pandemic, is acquiring new mutations in its genome. Although some mutations provide benefits to the virus against human immune response, others may result in their reduced pathogenicity and virulence. By analyzing more than 3000 high-coverage, complete sequences deposited in the GISAID database up to April 2020, here I report the uniqueness of the 28881–28883: GGG > AAC trinucleotide-bloc mutation in the SARS-CoV-2 genome that results in two substrains, described here as SARS-CoV-2g (28881–28883: GGG genotype) and SARS-CoV-2a (28881–28883: AAC genotype). Computational analysis and literature review suggest that this bloc mutation would bring 203–204: RG (arginine-glycine)>KR (lysine-arginine) amino acid changes in the nucleocapsid (N) protein affecting the SR (serine-arginine)-rich motif of the protein, a critical region for the transcription of viral RNA and replication of the virus. Thus, 28881–28883: GGG > AAC bloc mutation is expected to modulate the pathogenicity of SARS-CoV-2. These analyses suggest that SARS-CoV-2 has evolved into SARS-CoV-2a affecting COVID-19 infectivity and severity. To confirm these assumptions, retrospective and prospective epidemiological studies should be conducted in different countries to understand the course of pathogenicity of SARS-CoV-2a and SARS-CoV-2g. Laboratory research should focus on the bloc mutation to understand its true impacts on the course of the pandemic. Potential drug and vaccine development should also keep the 28881–28883 region of the N protein under consideration.